2023
DOI: 10.1055/s-0042-1758447
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange in inflammatory demyelinating disorders of the central nervous system: reasonable use in the clinical practice

Abstract: Plasma exchange (PLEX) is a therapeutic apheresis modality in which the plasma is separated from inflammatory factors such as circulating autoreactive immunoglobulins, the complement system, and cytokines, and its therapeutic effect is based on the removal of these mediators of pathological processes. Plasma exchange is well established for various neurological disorders, and it is applied successfully in central nervous system inflammatory demyelinating diseases (CNS-IDD). It mainly modulates the humoral immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(169 reference statements)
0
2
0
Order By: Relevance
“…Therapeutic plasma exchange serves as an extracorporeal blood purification technique used in treating various medical conditions [ 2 , 6 ]. This process involves separating plasma from whole blood and replacing it with either plasma or albumin to eliminate undesirable plasma components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic plasma exchange serves as an extracorporeal blood purification technique used in treating various medical conditions [ 2 , 6 ]. This process involves separating plasma from whole blood and replacing it with either plasma or albumin to eliminate undesirable plasma components.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic plasma exchange removes pathogenic factors in the serum, resulting in improvements in muscle strength, accelerated recovery, and reduced mechanical ventilation requirements [ 6 ]. A meta-analysis of six trials, which included 649 GBS patients (some ≥10 years of age), revealed the superiority of TPE over supportive care [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A typical PLEX cycle lasts two to three weeks and comprises five to seven cycles. However, this can vary as a meta-analysis by Queiroz et al mentioned in clinical practice that cycles can range from 5 to 15 for treatment response [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation in taking drugs with proven anti-inflammatory and antioxidant effects is their limited therapeutic range and safety profile. For example, corticosteroids are established as first-line drugs for the treatment of acute demyelinating attacks/exacerbations of MS [17,143,179,180]. Antioxidant effects have been established in MS patients, such as increased SOD activity and decreased ROS and MDA levels after methylprednisolone treatment [47,181,182].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant effects have been established in MS patients, such as increased SOD activity and decreased ROS and MDA levels after methylprednisolone treatment [47,181,182]. However, if patients do not respond to corticosteroid therapy, which occurs in 20-25% of MS cases, a second corticosteroid pulse therapy in combination with TPE is recommended after an interval of 10-14 days [169,180,183], or switching to TPE entirely when the adverse effects of corticosteroids are presented. The latter would have its clinical rationale in terms of affecting OS as well.…”
Section: Discussionmentioning
confidence: 99%